1999
DOI: 10.1103/physrevlett.83.5114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure on Tiny Antiferromagnetic Moment in the Heavy-Electron CompoundURu2Si2

Abstract: Effects of pressure on tiny antiferromagnetic moments in the heavy-electron compound URu2Si2 Amitsuka, H.; Sato, M.; Metoki, N.; Yokoyama, M.; Kuwahara, K.; Sakakibara, T.; Morimoto, H.; Kawarazaki, S.; Miyako, Y.; Mydosh, J.A.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
178
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(201 citation statements)
references
References 45 publications
17
178
6
Order By: Relevance
“…Furthermore, a variety of studies have shown that magnetism is found on the border of the hidden order state. For instance, measurements under applied pressure show that at P c ≈ 0.5 GPa, there is a first-order phase transition from hidden order to conventional antiferromagnetism, which is accompanied by destruction of the superconductivity [12][13][14]. Similar behaviour is observed with chemical pressure in the substitution series URu 2−x Fe x Si 2 [15].…”
Section: Introductionmentioning
confidence: 65%
“…Furthermore, a variety of studies have shown that magnetism is found on the border of the hidden order state. For instance, measurements under applied pressure show that at P c ≈ 0.5 GPa, there is a first-order phase transition from hidden order to conventional antiferromagnetism, which is accompanied by destruction of the superconductivity [12][13][14]. Similar behaviour is observed with chemical pressure in the substitution series URu 2−x Fe x Si 2 [15].…”
Section: Introductionmentioning
confidence: 65%
“…7,8 This implies that there is an implicit and common parameter leading to an equivalent effect in the different types of compression. In this subsection, we discuss the crystal strains caused by P and σ, and propose that the c/a ratio plays an important role in the competition between the two ordered phases.…”
Section: Discussionmentioning
confidence: 99%
“…We found from the neutron scattering experiments that µ o is strongly enhanced by applying pressure from 0.017 µ B /U (P = 0) to 0.25 µ B /U (P = 1.0 GPa). 7,8 In parallel, the 29 Si-NMR study revealed that the system is spatially separated into two differently ordered regions below T o : one is AF with a large moment and the other is non-magnetic. 9,10 The AF volume fraction is found to increase with P , roughly in proportion to µ 2 o (P ), while the magnitude of internal field is almost independent of P .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was found that non-Fermi liquid behavior, often associated with a quantum critical point, at which an ordering temperature is driven to 0 K, persists well into the ferromagnetic ordered phase that exists at moderate Re concentration in URu 2-x Re x Si 2 , a very unusual occurrence [10]. Early pressure studies on URu 2 Si 2 showed that applied pressure suppresses superconductivity, while the HO/AFM transition temperature is increased [11] and the measured moment grows substantially [12]. However, there still exist disagreements about the relationship between HO, AFM, and superconductivity as well as the general temperature-pressure phase diagram [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Early pressure studies on URu 2 Si 2 showed that applied pressure suppresses superconductivity, while the HO/AFM transition temperature is increased [11] and the measured moment grows substantially [12]. However, there still exist disagreements about the relationship between HO, AFM, and superconductivity as well as the general temperature-pressure phase diagram [12][13][14][15][16]. To more precisely map the pressure dependence of the hidden order and superconducting phases, electrical resistivity measurements on single crystals of URu 2 Si 2 are being performed as a function of temperature, magnetic field, and pressure.…”
Section: Introductionmentioning
confidence: 99%